ANALISIS PENERAPAN AKUNTANSI BIAYA LINGKUNGAN PADA PT. ROYAL COCONUT AIRMADIDI - Franciska, Regina Mariana; Sondakh, Jullie J.; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Environmental Accounting is an accounting science that has the function of identifying, measuring, valuing, recognizing, presenting, and disclosing costs incurred for the purpose of managing the environment. This study aims to determine the application of Environmental Cost Accounting at the company, in terms of identifying, measuring, presenting, and disclosing the Environmental Costs that exist in the company.The research was conducted at the PT. Royal Coconut Airmadidi. This study is a qualitative research. This study uses primary data and secondary data. The result of this research is the application of Environmental Cost Accounting in the company in terms of recognition, measurement, presentation, and disclosure of Environmental Cost has sealed with existing Financial Standars Accounting. But, the company has not made a specific Financial Statement.